Grape juices produced from new hybrid varieties grown on Brazilian rootstocks – Bioactive compounds, organic acids and antioxidant capacity - da Silva, Marlon Jocimar Rodrigues; da Silva Padilha, Carla Valéria; dos Santos Lima, Marcos; Pereira, Giuliano Elias; Filho, Waldemar Gastoni Venturini; Moura, Mara Fernandes; Tecchio, Marco Antonio (Food chemistry, 2019)
•Grape juices from southeast Brazil, an atypical region, were analyzed.•Grape juices produced from new hybrid varieties presented high antioxidant activity.•Polyphenol content of the grape juices was influenced by the rootstock.•Rootstock effect is dependent on the grape variety. The objective of this study was to assess the content of bioactive compounds, organic acids and antioxidant capacity of grape juices from Isabel Precoce, BRS Carmem, BRS Cora and IAC 138-22 Máximo varieties grown on the 'IAC 766’ and 'IAC 572’ rootstocks under tropical conditions in Brazil. In general, the color attributes of the 'Isabel Precoce' juice were inferior to those of the other juices due to their low anthocyanin content. In contrast, 'IAC 138-22 Máximo' juices showed the highest content of most individual anthocyanins, flavonols, trans-resveratrol and total phenolic compounds, and thus, higher antioxidant capacity. Except for 'BRS Carmem', all the juices presented higher sugar accumulation when 'IAC 766’ was used. This rootstock also contributed to the accumulation of t-resveratrol and most of individual anthocyanins in the 'IAC 138-22 Máximo' juices. However, the monomeric anthocyanin content was higher in 'BRS Carmem' juices when 'IAC 572’ rootstock was used.